Situational analysis of sickle cell disease in Gujarat, India - Deepak Saxena; Sandul Yasobant; Mahaveer Golechha (Wolters Kluwer Medknow Publications, 2017)
Background: Sickle cell disease (SCD) is a major public health concern in tribal community not only in Gujarat but also globally. Gujarat, a western state of India, has 89.12 lakh tribal populations and is expected to have at least 9,00,000 sickle cell trait and 70,000 SCD patients. The aim of the present review is to document the prevalence of SCD in various communities and various screening methods adapted. Methodology: An in-depth literature review was carried out using available search engines such as Cochrane Library, PubMed, Scopus etc. and published articles, and government reports/policy documents with reference to SCD were gathered. Results: A total of 17 original research articles and 2 policy/program documents are included in this review. The review suggests a prevalence of 0.6%-35% studies conducted among medical students, tribal schoolchildren, and tribal adolescents, with diverse screening methodologies. Conclusion: A diverse prevalence is observed in this review. Various screening methods such as dithionite turbidity test/hemoglobin/high-performance liquid chromatography methods were used to estimate the prevalence, citing the need for standardization. It was also found that not only tribal population, but also nontribal population have the risk of getting SCD that needs to be further investigated properly. Qualitative studies with SCD patients are required to understand the quality of life and morbidity pattern.